A novel approach to utilizing dredged materials at the laboratory scale. (27th December 2021) - Yu, Chunyang; Cui, Chunyi; Zhao, Jiuye; Zheng, Junjie
Graphical abstract: Highlights: Carbonation stabilization using steel slag is potentially a green method of utilizing dredged material. A combined treatment of foam drying and carbonation stabilization by alkaline modification of steel slag powder is proposed. The addition of steel slag powder stabilizes the foam in the slurry and reduces foam density more easily, thus promoting drying. The powdered steel slag is still active at a certain degree in carbonation stabilization after 24 h of drying. Abstract: The disposal and recycling of dredged materials (DM) are of great significance to sustainable development, and carbonation stabilization using steel slag is potentially a green method of utilizing DM. However, the underdeveloped dehydration process hinders the large-scale application of carbonation stabilization. Therefore, to find a more efficient and economical way of recycling DM, a continuous treatment combining the foam drying process with the carbonation stabilization process by introducing ground steel slag fist into dredged slurries was proposed. The effects of ground steel slag in the processes of foam drying and carbonation stabilization were individually assessed at the laboratory scale. The results showed that ground steel slag can stabilize the foam more easily and remarkably increase the drying rate. The optimum dry density of the foamed slurry is 0.60 g/mL, and the drying time is reduced by 58.3%. Ground steel slag is still active in the carbonation stabilization process after 24 h of drying. After carbonation stabilization, the maximum unconfined compressive strength of the modified soil reaches 2007 kPa, which is 8.5 times the value without carbonation stabilization. Moreover, it should be noted that the optimum moisture content for carbonation stabilization differs from that for compaction, which is an important distinction for practical application of the proposed technology. Through microscopic tests including X-ray diffraction (XRD), thermogravimetry (TG), and scanning electron microscopy (SEM), it is found that the strength of the modified soil derives from the carbonation reaction of steel slag. The product of carbonation stabilization is mainly spindle-shaped calcium carbonate with a particle size of <1 μm but a high degree of polymerization.